Engineering hydrology - Usul, Nurünnisa (ODTÜ Yayıncılık, 2024)
This book is the product of many long years of experience gained by delivering the subject matter in courses in Middle East Technical University and has been extensively revised in light of student interactions. Hydrology, an earth science, deals with the water on Earth: its occurrence, distribution, movement both on and under the surface, physical and chemical properties with their change in time and geographic location, as well as its relationship with the environment. Its subject matter places hydrology in close relation to other earth sciences such as meteorology, climatology, geology, oceanology, glaciology, limnology, cryology, potamology, etc. It is accepted as the fourth basic science for earth related engineering fields such as civil, geological, environmental, agricultural, etc. and used extensively in their applications, since water affects all forms of life and environment.